(untitled) (The Strategic Review for Southern Africa, 2020)
Binary thinking is one of the features of coloniality, manifesting in a zero-sum game between ‘our’and ‘their’security. The development of human securityas an antidote has, however, been marked bya continuation of such divisions in a much subtler way. This state of affairs is exacerbated bythe fact that concepts held up as possible solutions, such as the gendering of human securityor the broader tool of decolonisation, are often also trapped in unimaginative oppositional thinking which runs the risk of recolonising knowledge and harming those who are supposed to be secured. The focus in this article is therefore on the coloniality of human security scholarship and practices and how this concept can be reinvigorated through a feminist ‘post’-humanist lens. I argue that a feminist posthuman security approach that decentres the human (by going beyond asking for the inclusion of women only) and underscores agentic relations between (all) humans, the natural environment, technologyand objects more adequatelycaptures the entangled nature of human security practices, especially in the postcolony. The approach draws on a blend of six conceptual pillars, namely a poststructuralist understanding of agency as the product of intra-action rather than interaction; feminist critiques of equating what is male and what is human; the emphasis on intersections between race and gender in feminist postcolonial theory; the importance of situated knowledge; the agencyof matter and objects in the construction of securityand/ or insecurity; and an acknowledgement of indigenous Africacentred knowledge forms. I conclude that this kind of posthuman security frame, which merges feminist posthumanism and new materialist posthumanism, not only allows a more nuanced and inclusive understanding of the human condition but also offers a foundation for developing a decolonised human securityresearch agenda